Practical Prototype and script.aculo.us - Dupont, Andrew (Apress : Imprint: Apress, 2008)
As a JavaScript developer, you will already be aware of some of the time saving, convenience, and functionality provided to you by JavaScript/Ajax libraries in general. Prototype and its sister effects library, script.aculo.us, are among the most popular and best-supported JavaScript libraries, and now Prototype Core team member Andrew Dupont has written this book to provide you with an essential guide to getting the most out of using Prototype and script.aculo.us. Practical Prototype and script.aculo.us will help you leverage the Prototype and script.aculo.us libraries to enhance your day-to-day work, speeding up mundane tasks and providing advanced user interface effects in a way that is cross-browser compliant-taking many worries off your shoulders. Take a whirlwind tour of the different time-saving functions and features Prototype provides and how it extends the basic JavaScript objects, including events, Ajax techniques, DOM elements, enumerables, and advanced object-oriented programming. Understand how script.aculo.us fits into the wider world of DOM Scripting/DHTML; find out how to use it to enhance your user interfaces quickly and effectively, with UI controls, effects, and drag and drop; and discover Prototype and script.aculo.us as a platform. The author avoids needless theory and rhetoric throughout the book, moving you through the topics at a fast pace. He incorporates several real-world examples to help you gain valuable practical experience as you learn. Practical Prototype and script.aculo.us is completely up to date and features server-side examples written in PHP that show the framework can be used effectively in more environments than just Ruby on Rails. Master all the convenience functions of Prototype to speed up your JavaScript/Ajax development Leverage script.aculo.us to turbo charge your dynamic UIs Learn from JavaScript expert Andrew Dupont, one of the Prototype Core team members.